2020
DOI: 10.1017/s000711452000330x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of micronutrients as a possible and modifiable risk factor for COVID-19: a UK perspective

Abstract: Recent scientific evidence has indicated that the elderly have increased risk of COVID-19 infections, with over-70s and 80s being hardest hit—especially residents of care homes and in clinical settings, ethnic minorities, people who work indoors and those who are overweight and obese. Other potential risk factors include lack of exposure to sunlight, darker skin pigmentation, comorbidities, poor diet, certain medications, disadvantaged social and economic status, and lifestyle factors such as smoking and exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 61 publications
(93 reference statements)
0
82
1
2
Order By: Relevance
“…Closer studies are needed to elucidate the reasons behind various observed changes, focusing on availability of foods, stress-related eating and other factors, affecting behavior such as media recommendations and science news. Following those information, particular attention has been paid to the intake of micronutrients, including vitamin C and D during COVID-19 pandemic [44,45], since increased intake of fruit and vegetables has been recommended by several authors, in order to support the immune system [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Closer studies are needed to elucidate the reasons behind various observed changes, focusing on availability of foods, stress-related eating and other factors, affecting behavior such as media recommendations and science news. Following those information, particular attention has been paid to the intake of micronutrients, including vitamin C and D during COVID-19 pandemic [44,45], since increased intake of fruit and vegetables has been recommended by several authors, in order to support the immune system [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic generates a great interest in dietary advice, supplements, nutraceuticals, and complementary/alternative medicine (CAM) in order to improve immune function [ 170 , 230 , 231 , 232 ]. However, there is no evidence for their efficacy in COVID-19 [ 170 , 230 , 231 ] and further studies are needed before giving public messages [ 170 , 231 , 232 ] in order to avoid potential adverse effects of CAM [ 232 ]. It has been reported that Chinese migrant women with GDM were more prone to supplementation use compared with Australian-born white women [ 233 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that omega-3 polyunsaturated fatty acids (omega-3 PUFA), vitamins (folate, A, B6, B12, C, D, and E) and minerals (copper, iron, magnesium, selenium, and zinc), improve the immune system [ 167 , 168 , 169 , 170 , 171 , 172 , 173 ]. Although supplementations with omega-3 PUFA and/or micronutrients have been suggested to improve clinical outcomes of patients with ARDS [ 174 , 175 , 176 , 177 ] and to improve public health [ 167 , 177 ], it has been pointed out that only individuals at high-risk of specific nutrient deficiencies could benefit from supplementation, whereas the supplementation of a single nutrient is not promising in the general population [ 178 ].…”
Section: Mechanisms Of the Mediterranean Diet Componentsmentioning
confidence: 99%
“…Quality and dietary diversity of food insecure households are lower than food secure ones (25,26) . A healthy diet that provides the micronutrients needed by the body contributes to the better functioning of the immune system (27) . Low-quality diets cause a lack of vital micronutrients for proper body function (28) .…”
Section: Discussionmentioning
confidence: 99%